2020
DOI: 10.1007/s00520-020-05345-9
|View full text |Cite
|
Sign up to set email alerts
|

Cryotherapy for the prevention of weekly paclitaxel-induced peripheral adverse events in breast cancer patients

Abstract: Purpose This randomized phase II study was conducted to investigate the efficacy of cryotherapy in preventing peripheral neuropathy and dermatological adverse events in breast cancer patients treated with weekly paclitaxel. Methods Patients treated with 12 weekly doses of paclitaxel for breast cancer were randomized (1:1) into a cryotherapy or control group. The primary endpoint was the percentage of patients with a marked decrease in the Functional Assessment of Cancer Therapy-Neurotoxicity (FACT-NTX) score. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 26 publications
0
39
0
4
Order By: Relevance
“…Firstly, by permitting periods of temporary cryotherapy interruption for intolerant patients, all subjects in our study had removed their devices at least once regardless of reasons. In comparison, the Japanese study reported that 68% of their patients were able to wear the hypothermia gloves and socks without interruption, and further analysis revealed greater cryotherapy benefits among these patients (20). This suggests that the continuous application of cryotherapy may be critical to produce a sustained benefit in preventing CIPN.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Firstly, by permitting periods of temporary cryotherapy interruption for intolerant patients, all subjects in our study had removed their devices at least once regardless of reasons. In comparison, the Japanese study reported that 68% of their patients were able to wear the hypothermia gloves and socks without interruption, and further analysis revealed greater cryotherapy benefits among these patients (20). This suggests that the continuous application of cryotherapy may be critical to produce a sustained benefit in preventing CIPN.…”
Section: Discussionmentioning
confidence: 99%
“…Existing randomized controlled trials that utilized the same Elasto-Gel TM hypothermia devices reported potential reduction in neuropathic symptoms with cryotherapy (19,20). Less sensory and motor symptoms with cryotherapy was observed in one Japanese study (20), and less neuropathic symptoms leading to improved quality of life was observed in another study (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1724 Additionally, exposure to cryotherapy treatment ranged from 90 minutes to 210 minutes and some studies required changing insulators every 45-60 minutes. 1626 In addition to frozen gloves and socks, cryotherapy was also assessed using continuous limb cooling, application of crushed ice, and simultaneous compression and cryotherapy. 16 , 25 , 26 Differences in cryotherapy administration methods make it challenging to determine which is the most safe and efficacious, reinforcing the need for better designed, larger trials that utilize consistent cryotherapy techniques to identify the most effective and well tolerated method of cryotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 11 studies were included in the final review (Table 1). [16][17][18][19][20][21][22][23][24][25][26] Literature review The average age of patients in the cryotherapy group was 53. At the end of 12 weeks, there was no difference in the AUC of the CIPN-20 scores between the two groups.…”
Section: Study Selectionmentioning
confidence: 99%